Crystal structure of 1, 7, 8, 9-tetrachloro-4-(3, 5-dichlorobenzyl)-10, 10-dimethoxy-4-azatricyclo[5.2.1.02, 6]dec-8-ene-3, 5-dione. (January 2015) - Liu, He; Zhong, Jia-liang; Sun, Wen-xia; Gong, Yan-qing; Liu, Li-hong
No abstract available